2018
DOI: 10.1111/jcmm.13741
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for IκB kinases alpha and beta in regulating pulmonary endothelial angiogenic function during late lung development

Abstract: Pulmonary angiogenesis is essential for alveolarization, the final stage of lung development that markedly increases gas exchange surface area. We recently demonstrated that activation of the nuclear factor kappa‐B (NFκB) pathway promotes pulmonary angiogenesis during alveolarization. However, the mechanisms activating NFκB in the pulmonary endothelium, and its downstream targets are not known. In this study, we sought to delineate the specific roles for the NFκB activating kinases, IKKα and IKKβ, in promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 58 publications
0
15
2
Order By: Relevance
“…Although important for alveolarisation, it is not a major focus of this review. In mice, important mediators include vascular endothelial growth factor (VEGF) , nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) , insulin‐like growth factors , and platelet endothelial cell adhesion molecule (PECAM‐1) . Vegfa mRNA expression peaks during alveolarisation .…”
Section: Mesenchymal Cells and Angiogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Although important for alveolarisation, it is not a major focus of this review. In mice, important mediators include vascular endothelial growth factor (VEGF) , nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) , insulin‐like growth factors , and platelet endothelial cell adhesion molecule (PECAM‐1) . Vegfa mRNA expression peaks during alveolarisation .…”
Section: Mesenchymal Cells and Angiogenesismentioning
confidence: 99%
“…NF‐κB is constitutively active in neonatal developing endothelium and is needed for survival and proliferation of endothelial cells . Inhibiting NF‐κB or its activating kinases leads to impaired angiogenesis in vitro , and loss of distal pulmonary vessels and alveolar simplification in vivo . It has been suggested that disrupted alveolarisation in PECAM‐1 null mice may be caused by impaired endothelial cell motility .…”
Section: Mesenchymal Cells and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…PEC were transfected NTC, integrin aV, integrin b3, or Csf3 On-Target Plus SMART pool siRNA using Lipofectamine 2000 for 6h as previously described (21).…”
Section: Rna Interferencementioning
confidence: 99%
“…4D). Further, we performed studies using PEC obtained from mice containing an endothelial-specific deletion of IKKb, the primary activator of NFkB in early alveolar PEC (21). Although rTGFBI increased migration in WT PEC (P<0.01), TGFBI-induced migration was absent in PEC lacking IKKb.…”
Section: Tgfbi-mediated Pec Migration Is Nfκb-dependentmentioning
confidence: 99%